2012
DOI: 10.1213/ane.0b013e318256486c
|View full text |Cite
|
Sign up to set email alerts
|

Using Time-Frequency Analysis of the Photoplethysmographic Waveform to Detect the Withdrawal of 900 mL of Blood

Abstract: A time-frequency spectral method detected blood loss in spontaneously breathing subjects before the onset of significant changes in heart rate or blood pressure. Spectral amplitudes at the heart rate frequency band were found to significantly decrease during blood loss in spontaneously breathing subjects, whereas those at the breathing rate frequency band did not significantly change. This technique may serve as a valuable tool in intraoperative and trauma settings to detect and monitor hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…Lower PPGAmin and higher PPGAvar also correlated with higher amounts of intravenous fluids received which is in line with volume depletion effects on PPG described in previous studies on healthy volunteers [18,19]. Due to the limits of the methodology used in data collection, no true beat to beat variation was calculable of the data.…”
Section: Discussionsupporting
confidence: 86%
“…Lower PPGAmin and higher PPGAvar also correlated with higher amounts of intravenous fluids received which is in line with volume depletion effects on PPG described in previous studies on healthy volunteers [18,19]. Due to the limits of the methodology used in data collection, no true beat to beat variation was calculable of the data.…”
Section: Discussionsupporting
confidence: 86%
“…We have demonstrated this potential by respiration rate detection with the VFCDM-FM method [13] and HRV analysis. Assessment of R-R intervals has recently been shown to be an accurate way of detecting episodes of atrial fibrillation [8], and the VFCDM method has recently been shown to be capable of detecting significant levels of blood volume loss from a PPG signal [9, 10]. In the present letter, the proof-of-concept we have shown opens the door to implementing these algorithms on a mobile phone platform using simply the optical recordings of the phone.…”
Section: Discussionmentioning
confidence: 83%
“…Hemorrhage is the most prevalent cause of death from injuries sustained on the battlefield and comprises approximately 90% of the causes of Bpotentially survivable[ death (20). The main disadvantage of currently used vital signs is that they are relatively insensitive to small amounts or rates of blood loss (10,23). This scenario leaves the point-of-injury caregiver charged with the difficult task of promptly identifying bleeding casualties in need of rapid evacuation without reliable differences in their clinical presentations or standard vital signs or the benefit of imaging.…”
Section: Discussionmentioning
confidence: 99%